La structure factorielle de la version français de l'Échelle d'adjustemente dyadique - Bouchard, Guylaine; Sabourin, Ph. D, Stéphanie; Lussier, Yvan; Wright, John; Boucher, Colette (Canadian Journal of Counselling and Psychotherapy, 2011)
The main purpose of the present study was to determine the factorial structure of the Dyadic Adjustment Scale (DAS) in its French version. More specifically, we tried to replicate the DAS factors in a clinical sample of distressed couples. The DAS is a marital distress questionnaire designed to assess four areas of dyadic adjustment: dyadic cohesion, dyadic consensus, dyadic satisfaction and affectional expression. The sample consisted of 72 couples seeking marital therapy at the Université de Montréal psychology clinic. Results showed that the DAS global score is reliable. However, they cast doubt on the reliability of the satisfaction and affective expression subscales. In addition, the multidimensional factor structure of the DAS was not replicated in the present clinical sample of distressed couples. The clinical use of the DAS factor scores appears premature; future studies should be conducted to assess the factorial invariance of the DAS.